Manajemen Layanan Sepatu Jolifa (Sistem Perpustakaan Jogja Library For All) Balai Layanan Perpustakaan DPAD Daerah Istimewa Yogyakarta - Adzkiyah Mubarokah; Labibah Zain (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Sepatu Jolifa (Jogja Library Integrated Library System Service for All), is a network system that contains information and library collections that can be accessed online by the public, where this system will contain various information and collections from various libraries in Yogyakarta, so that a system that integrates libraries in Yogyakarta, the management system of this system is very interesting to study how all libraries can be connected to one another. This study used a qualitative research method with a descriptive approach. Information in writing was obtained using interview techniques, observation and documentation. The purpose of this study is to describe how the management of Sepatu Jolifa, which is a library tarpaulin service system, can work with a tub. The results of this study show that the management process for Sepatu Jolifa begins with the Planning and Decision Making process, then Organization, Staffing, Direction and Supervision, and Controlling Co-Ordination. In addition, in the process of managing Sepatu Jolifa, they also continue to maintain Communication, Motivation, Leadership Social Responsibilities of Business Strategic Management so that the management of Jolifa Shoes can continue to run well.